Erinnerungskulturen post-imperialer Nationen - Rothermund, Dietmar (Nomos, 2015)
"Brings together the varying perspectives with historians attempting to bind memory and its experience of different post-imperial nations -- Britain, Netherlands, France, Belgium, Italy, Portugal and Japan"--Provided by publisher
Literaturangaben und Index
Engl. Ausg.: Memories of post-imperial nations : the aftermath of decolonization, 1945-2013 / edited by Dietmar Rothermund. Daryaganj, Delhi, India : Cambridge University Press 2015
Keywords: Europe -- Colonies -- Congresses; Konferenzschrift -- 2013 -- Heidelberg; Hochschulschrift; Geschichte 1945-2013; Geschichtsschreibung; Kolonialmacht; Entkolonialisierung; Kongress; Postkolonialismus; Imperialismus; Kollektives Gedächtnis; Geschichtsbild; Gedächtnis; Nation; Nationalstaat; Rothermund, Dietmar